EFFECTIVENESS OF NON-PHARMACOLOGICAL COMMUNITY-BASED NURSING INTERVENTIONS FOR SMOKING CESSATION IN ADULTS: STUDY PROTOCOL OF A SYSTEMATIC REVIEW - TERZİ, Handan; KİTİS, Yeter; AKIN, Belgin (Holistence Publications, 2019)
Tobacco use is one of the common and preventable risk factors of non-communicable diseases. Although the smoking rates tends to be decreased thanks to universal policies, it still is not satisfactory, especially among the middle-aged individuals In order to achieve success in smoking cessation activities, it is crucial to determine the most effective nursing interventions and apply them into the practice. The objective of this systematic review is to investigate the effectiveness of non-pharmacological community-based nursing interventions for smoking cessation on cessation rate, non-relapsing rate and knowledge belief and attitude related to smoking in over 45 year-olds living in the community. PubMed, Cochrane Library, EMBASE, PsycINFO, Cochrane Central Register of Controlled Trials (CENTRAL), EBSCO, ProQuest, Academic Search Complete, Ovid, CINAHL Plus with Full Text, MEDLINE, Web of Science, Scopus, Turkish Council of Higher Education Thesis Center, Ulakbim Turkish Medical Database and Turkiye Citation Index were searched. Databases were searched from the 1st of January 2008 to the 31st of December 2017. Languages were Turkish and English. The protocol of this systematic review was registered to PROSPERO database. The registration number is CRD42018088007. The study is ongoing. The databases were searched and 796 studies were retrieved in total. The quality assessment process is ongoing. The data to be gathered from this systematic review is predicted to be a source for both primary care nurses and the other primary care professionals in terms of the effective smoking cessation method, its duration and changes in knowledge belief and attitude of individuals. The smoking cessation interventions performed actively by primary care nurses, will facilitate to reach both local and global targets for preventing the non-communicable diseases. It is also aimed to contribute to nursing education curriculum by revealing the roles and influence of primary care nurses on smoking cessation promotion.
Keywords: 4. Education; 3. Good health